Analisis Intensi Penggunaan Akuntansi Berbasis Cloud pada Usaha Kecil dan Menengah Berdasarkan Model Unified Theory of Acceptance and Use of Technology - Mareta Deswana Putri; Pigo Nauli (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This research is motivated by the increasing need for efficient, flexible, and relatively low-cost accounting systems among Small and Medium Enterprises (SMEs). Cloud-based accounting is seen as being able to help SMEs improve accuracy, reporting speed, and financial decision-making. However, its utilization rate remains suboptimal. The purpose of this study is to analyze the influence of performance expectancy, effort expectancy, social influence, and facilitating conditions on the intention to use cloud-based accounting in SMEs using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This study employed a quantitative approach with primary data collected through questionnaires from SMEs using cloud-based accounting. This data was analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) to test the measurement and structural models.The results show that performance expectancy, effort expectancy, and social influence have a significant positive effect on the intention to use cloud-based accounting, while facilitating conditions have a positive but not always significant effect on the intention to use. Therefore, the main variables driving intention to use are belief in the benefits, ease of use, and social support. The implications of this research emphasize the importance of developers and providers of cloud-based accounting services to improve features that support performance, clarify ease of use, and utilize social outreach and social recommendation strategies, while policy makers and business associations need to provide training and infrastructure support so that the adoption of cloud-based accounting in SMEs can increase.